2016
DOI: 10.1002/ejic.201601148
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Switching of Copper Complexes with Quaterpyridine

Abstract: Chemically and electrochemically induced interconversion between five one-stranded complexes of copper(II) and the respective double-stranded helicates of copper(I) bearing the ligand 6,6′′′-dimethyl-2,2′:6′,2′′:6′′,2′′′-quaterpyridine (L) culminated in different luminescence properties. Five new mononuclear complexes of copper(II) bearing the ligand L {[Cu II LCl 2 ] (1), [Cu II L(ClO 4 ) 2 ] (2), [Cu II L(NO 3 ) 2 ] (3), [Cu II L(CF 3 SO 3 ) 2 ] (4), and [a] 861 [a] Standard uncertainties are given in parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The [Cu 2 L 2 ] 2+ ↔ 2­[Cu L ] 2+ interconversion has been monitored electrochemically for L = 5 , 17 , 26 , and 73 and was discussed in detail in a recent tutorial review and by us . It should be noted that, in some cases, it was possible to observe unstable intermediates such as [Cu (II) 2 ( L ) 2 ] 4+ species.…”
Section: Architecture Of Qtpy Coordination Complexesmentioning
confidence: 99%
“…The [Cu 2 L 2 ] 2+ ↔ 2­[Cu L ] 2+ interconversion has been monitored electrochemically for L = 5 , 17 , 26 , and 73 and was discussed in detail in a recent tutorial review and by us . It should be noted that, in some cases, it was possible to observe unstable intermediates such as [Cu (II) 2 ( L ) 2 ] 4+ species.…”
Section: Architecture Of Qtpy Coordination Complexesmentioning
confidence: 99%
“…27 The reduction peaks are associated with the reverse peaks at E pa À75 mV, À90 mV and À365 mV for 2, 3 and 4 respectively, attributed to the Cu(I) / Cu(II) process. The Cu(II) / Cu(I) reduction is probably associated with the change of coordination geometry of metal center what leads to disassembling/assembling process, 28 as well as to the formation of a solvated copper(I) species with acetonitrile molecules, since this solvent forms stable Cu(I)-acetonitrile complexes in solution. 29 The presence of solvated copper(I) ions in solution is supported by the broad peaks at about +750 mV, +525 mV and +765 mV for 2, 3 and 4 respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Amendola et al reported the Cu II/I couple with the (1 E ,1′ E )- N , N ′-[(1 S ,2 S )-cyclohexane-1,2-diyl]­bis­[1-(quinolin-2-yl)­methanimine] ligand; the results of X-ray single-crystal diffraction show that (Cu 2 I L 2 ) 2+ and (Cu II L) 2+ are stable structures, and CV measurements reveal that (Cu I L) + and (Cu 2 II L 2 ) 4+ are unstable . Adamski et al studied the Cu II/I couple with the 6,6‴-dimethyl-2,2′:6′,2″:6″,2‴-quaterpyridine ligand, and they also supported that (Cu 2 I L 2 ) 2+ and (Cu II L) 2+ are stable structures …”
Section: Introductionmentioning
confidence: 95%
“…25 Adamski et al studied the Cu II/I couple with the 6,6‴-dimethyl-2,2′:6′,2″:6″,2‴quaterpyridine ligand, and they also supported that (Cu 2 I L 2 ) 2+ and (Cu II L) 2+ are stable structures. 26 In this work, the two ligands 1,3-bis(2,2′-bipyridin-6yloxy)propane (La) and 1,3-bis[(6′-methyl-2,2′-bipyridin-6yl)oxy]propane (Lb) and their Cu(I) complexes Cu I La and Cu I Lb were synthesized. Their solutions were characterized by electrospray ionization mass spectroscopy (ESI-MS) and 1 H NMR spectroscopy.…”
Section: ■ Introductionmentioning
confidence: 99%